Genetic and biochemical diversity of terpene biosynthesis in cyanobacterial strains from tropical soda lakes - Machado, Mauricio J.; Jacinavicius, Fernanda R.; Médice, Rhuana V.; Dextro, Rafael B.; Feitosa, Anderson M. T.; Weiss, Marcio B.; Pellegrinetti, Thierry A.; Cotta, Simone R.; Crnkovic, Camila M.; Fiore, Marli F. (Frontiers in Microbiology, 2025)
IntroductionTerpenes and terpenoids are vital components in diverse metabolic pathways, forming the terpenome—the complete spectrum of terpene-related compounds biosynthesized by an organism. Integrating bioinformatic tools has significantly enhanced the ability to assess metabolic potential by combining these computational approaches with experimental biochemical data. Furthermore, gene annotation provides critical insights into specialized targets, facilitating the identification of shared or unique features across different strains.Aims and methodsThis study investigates the presence of terpene compounds in cyanobacterial strains isolated from tropical soda lakes using a combination of gene mining, synteny analysis, phylogenetics, and metabolomics.Results and discussionKey enzymes, including phytoene synthase and squalene hopene cyclase, were identified, showing significant similarities and evolutionary links to gene copies in Cyanobacteria from diverse ecological environments. Metabolomic analysis complemented genomic predictions, uncovering a rich diversity of tetraterpene compounds, particularly carotenoids. Notably, triterpene hopanoids were found exclusively in a unicellular strain. These compounds show significant potential for cellular protection, metabolic adaptation, and biotechnological uses. They might support microbial communities in extreme environments, such as the saline-alkaline lakes of the Pantanal Biome in Brazil, developing unique survival and resilience strategies in these harsh conditions.ConclusionThis study highlights the extensive range of insights that can be obtained by integrating genetics and biochemistry in exploring cyanobacterial diversity, especially from organisms thriving in extreme environments.